CONCEPT MAPPING AS A MEANS OF TEACHING VOCABULARY (EDUCATION IN THE 21ST CENTURY, 2023)
Language is an important means of communication with the help of which one can express his ideas, feelings, convey information either orally or in a written form. As Rupley, Logan and Nichols(1999) mentioned, vocabulary is the glue that holds stories, and content together making comprehension accessible for learners. Vocabulary teaching is of utmost importance as without sufficient vocabulary knowledge it is impossible to communicate. The problem is how to make vocabulary teaching more effective and challenging as students have difficulty in memorizing lists of words. The problems encountered in reading, writing, speaking and listening are mainly because of insufficient vocabulary knowledge. To solve this problem and make vocabulary teaching more interesting and enjoyable it is necessary to look for new techniques which will make vocabulary memorization easier. We think that such an effective way is the concept map usage. Concept maps are more effective than conventional methods for teaching new words to help students acquire the ability to determine word meaning use words in sentences.
Keywords: Keywords: concept mapping, teaching vocabulary, increasing motivation, experiment.; concept mapping, teaching vocabulary, increasing motivation, experiment.; concept mapping; teaching vocabulary; increasing motivation; experiment; study